Management of Acute Bleeding Upper GI Ulcers in the Era of Endoscopic and IV PPI Therapy - Alexandra Ilnyckyj; George Mathew (Canadian Journal of Gastroenterology)
BACKGROUND: Despite advances in therapy, the morbidity and mortality of gastrointestinal bleeding remains high. A review of current practice patterns was undertaken in St Boniface General Hospital, Winnipeg, Manitoba to assess the standard of care provided.